P4.061 Physical Activity and Risky Sexual Behaviour in Men Who Have Sex with Men and Heterosexual Males in Tel Aviv, Israel. (13th July 2013) - Mor, Z; Parfionov, K; Davidovitch, N; Grotto, I
Abstract : Background: Men who have sex with men (MSM) who exercise intensive anaerobic training (IAT) become muscular and physically-attractive, are increasing the number of potential sex-partners and their risk for STI/HIV. This study compared training practises between MSM and heterosexuals, and explored factors associating IAT with sexual-behaviour. Methods: This cross-sectional study included a convenient sample of men from 5 Tel-Aviv gyms, who completed anonymous questionnaires regarding their physical training, health and sexual behaviour. Trainees who exercised more than the median anaerobic training-hours were regarded as IAT, and those who performed > one unprotected anal/vaginal-intercourse in the last six months were defined as sexual-risky. Results: In 2011, 184 (48%) MSM and 197 (52%) heterosexuals completed the questionnaire. MSM showed a stronger desire to become muscular than heterosexuals, reported more weekly hours of IAT (5.0 and 3.9, respectively, p < 0.001) and used protein-powers or anabolic-steroids more commonly than heterosexuals. MSM reported that the main reasons for training were refining body-shape and improving self-confidence, while heterosexual indicated that weight-loss and health improvement were the main reasons for training. MSM were more sexual-risky than heterosexuals. Of all sexual-risky, 61.9% (N = 70) performed IAT, while 38.1% (N = 43) perform moderate anaerobic training, p < 0.01. This association was stronger among MSM than in heterosexuals ( p < 0.01 vs . p = 0.05, respectively). In multivariate analysis, MSM, younger age, dissatisfaction from body shape, strong desire to be more attractive, higher sexual obsession-score, and the use of protein supplement powders predicted an IAT The interaction between MSM and IAT among risky participants was multiplicative. Discussion: MSM practised more IAT than heterosexuals, and their interaction between IAT and sexual-risk was multifactorial. MSM community can benefit from holistic approach of sexual-health, addressing body-image and IAT. The gym gay-culture demonstrates how internal dynamics and social norms are possible factors driving MSM to high-risk for HIV.